2008
DOI: 10.3858/emm.2008.40.6.639
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional induction of DLC-1 gene through Sp1 sites by histone deacetylase inhibitors in gastric cancer cells

Abstract: We previously reported that trichostatin A (TSA), a histone deacetylase (HDAC) inhibitor, induced DLC-1 mRNA expression and accumulated acetylated histones H3 and H4 associated with the DLC-1 promoter in DLC-1 non-expressing gastric cancer cells. In this study, we demonstrated the molecular mechanisms by which TSA induced the DLC-1 gene expression. Treatment of the gastric cancer cells with TSA activates the DLC-1 promoter activity through Sp1 sites located at -219 and -174 relative to the transcription start … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Several studies have shown interactions of Sp1 with a variety of proteins, including p107, class I HDACs (HDAC1, HDAC2, and HDAC6), p300, and CBP (20,24,25,28,34,53,61). Modulation of the interactions between Sp1 and these partner proteins has been shown to be crucial for the regulation of Sp1-dependent gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown interactions of Sp1 with a variety of proteins, including p107, class I HDACs (HDAC1, HDAC2, and HDAC6), p300, and CBP (20,24,25,28,34,53,61). Modulation of the interactions between Sp1 and these partner proteins has been shown to be crucial for the regulation of Sp1-dependent gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that corepressors such as HDAC1, HDAC2, and HDAC6 may be recruited by Sp1 to repress gene expression (7,9,25,34). On the other hand, coactivators such as p300 and CBP also could be recruited by Sp1 to the promoters to transactivate gene expression (20,28). We sought to determine which corepressors or coactivators interact with Sp1.…”
Section: Fig 4 Dna Binding Ability Of Sp1 Is Essential For Zp Activmentioning
confidence: 99%
“…5-Aza-dC has previously been shown to induce overexpression of TSGs by decreasing DNA methylation levels [21,22]. TSA increases the pool of acetylated histones and also induces the overexpression of some TSGs in embryonic stem cells [23,24]. In recent reports, histone H3 lysine 9 (H3K9) methylation and DNA methylation were considered to be the causes of TSG silencing [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study providing clues for the mechanism responsible for the induction of DLC1 expression through HDAC-mediated chromatin modifications demonstrated that TSA activates DLC1 promoter in gastric cancer cells and that Sp1 binding sites are required for promoter activation (13).…”
Section: Discussionmentioning
confidence: 99%